Can black swans be tamed with a flexible mean‐variance specification?. (30th October 2020) - Chatzikonstanti, Vasiliki; Karoglou, Michail
Abstract: We examine the homogeneity of the highly improbable returns, what practitioners and the mainstream economic press also call black swan events. By setting up a simple framework and using the benchmark stock market indices of all OECD countries, we find that the frequency of black swans varies greatly over the last two decades often with dramatic changes that can be related to major economic events. Moreover, during the global financial crisis, black swans were substantially more frequent for most countries even after controlling for the level of volatility. This implies that, despite the plethora of appropriate financial instruments to counter this effect, during an obvious economic turmoil, stock markets are still more likely to experience highly improbable events.